Pengaruh Penggunaan Modifikasi Standar Resep Lauk Nabati Tempe terhadap Daya Terima dan Persepsi Pasien Rawat Inap - Dewi Renaningtyas; Endy Paryanto Prawirohartono; Susetyowati Susetyowati (Jurnal Gizi Klinik Indonesia, 2004)
Background: Food management is inseparable part of all efforts to cure hospitalized patients. If patient is not able to consume enough food, nutrient deficiency will occur. This condition results in delayed recovery of illness, lengthen length of stay, therefore hospital charges will increase. According to previous observations, there is a significant plate waste due to several reasons. To minimize the negative effect of plate waste on diet therapy, standard of recipes should be applied.Objective: To analyze the influence of the modification of recipes standard of fermented soybean on patient’s acceptance and perception.Methods: We conducted a cross-over design study in Dr. Sardjito Hospital Yogyakarta. The subjects were adults patients who admitted to the Departments of Surgery and Obstetrics and Gynecology. The inclusion criteria were hospitalized more than 4 days, over 15 years old, not in severe illness, got ordinary diet, and signed an informed consent. The food acceptance was measured as plate waste that was weighed using a special scale with accuracy of 10 grams. Food perceptions were measured using a questionnaire. Data were analyzed using chi-square test and Spearman correlation test.Results: Among 132 patients, 112 (84,8%) patients had good acceptance to the modified recipes compared to 20 (15,2%) patients who had poor acceptance, whereas only 66 (50%) patients from standard recipes had good acceptance to standard recipes, and this difference was statistically significant (p=0,006). There were 99 (75%) patients from modified recipes who had good perceptions to modified recipes compared to 18 (13,6%) patients from standard recipes who had good perceptions to standard recipes, and this difference statistically significant (p=0,003).Conclusions: Patients from surgery and obstetric and gynecology wards prefer modified recipes of fermented soybean compared to standard recipes.